Genotypic identification of oral bacteria using 16s rRNA gene in children with and without early childhood caries in Kelantan - Al-Hudhairy, Salahddin Abdulqader Othman (2016)
Oral microorganisms are considered as one of the primary aetiological factors in Early Childhood Caries (ECC) but they have not been completely identified. The present study aimed to identify oral bacterial genotypes in 12 caries-free children (CF) and 36 children with ECC aged 71 month and below by using 16S ribosomal RNA gene sequence. In ECC children, plaque and dentine samples were collected from intact enamel surfaces, over cavitated lesion and from dentine lesion surface. For CF children, plaque samples were collected from sound tooth surfaces at baseline and after one year follow up. The genomic DNA was extracted from all samples, subjected to 16S rRNA PCR amplification and the end products were cloned into pCR®2.1-TOPO® Vector. Five randomly selected positive clones collected from each surface were sent for sequencing. Identification of the bacterial clones was performed using BLAST search against GeneBank database. A total of 660 clones were collected from enrolled children. From ECC group, 540 clones were obtained from three different surfaces while, in CF group, 120 clones were collected from sound tooth surfaces at baseline and after one year. Several comparisons were performed between those identified oral bacteria using Pearson Chi-square test or Fisher’s exact test between different categorical variables, while McNemar test was used to compare among the individual categories. A total of 39 oral bacterial generawere identified from the ECC group. At genus level, Streptococcus sp. was the most predominant bacteria among ECC group. Fusobacterium sp. is significantly higher in the intact enamel while Lactobacillus sp. is significantly higher in the dentine surface (p < 0.05). At species level, Fusobacterium nucleatum subsp. polymorphum was detected in the intact surface (33.3%) while Streptococcus mutans was detected over the carious lesions and dentine (33.3% and 52.7% respectively). A total 18 oral bacteria genera were identified from CF group at baseline and after 1 year follow up, but there were no significant differences between groups. At species level, Fusobacterium nucleatum subsp. polymorphum is found highest in the CF group. After follow up, Corynebacterium matruchotii is highest in those who remained caries free, while Porphyromonas catoniae is highest in those who developed caries. In conclusion, Streptococcus sp. is strongly associated with caries progression in children with ECC especially for Streptococcus mutans. Lactobacillus sp. is restricted to deep carious lesions. Fusobacterium sp., Leptotrichia sp., and Corynebacterium sp. may play a role in sustaining the healthy environment.